Pengaruh Fasilitas Dan Kepuasan Kerja Terhadap Kinerja Pegawai Puskesmas Rambang Kapak Tengah (RKT) Prabumulih - Hesinto, Sebri; Ramayani, Rika Fitri; Purnamasari, Widya (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
The identification results show a phenomenon at the Rambang Kapak Tengah Health Center in Prabumulih City because it only has a few rooms with facilities such as AC in the pharmacy room and the management room. This problem makes employees uncomfortable in working and decreases job satisfaction. The results of this study partially (t-test) Facilities (X1) have a positive and significant effect on Performance (Y), and Job Satisfaction (X2) has a positive and significant effect on Performance (Y). While simultaneously (F test) Facilities (X1) and Job Satisfaction (X2) have a positive and significant effect on Performance (Y), the correlation between Facilities and Employee Performance is strong, positive (unidirectional). In contrast, the correlation between Job Satisfaction and Employee Performance is negative (not unidirectional). The coefficient of determination (R2) shows that Employee Performance is influenced by Facilities and Job Satisfaction followed by Employees. The rest is influenced by other variables, such as leadership, compensation, motivation, and other variables, on employee performance.Kata Kunci : Fasilitas, Kepuasan kerja, Kinerja Pegawai